2019
DOI: 10.1088/1758-5090/ab063f
|View full text |Cite
|
Sign up to set email alerts
|

Microbial transglutaminase induced controlled crosslinking of gelatin methacryloyl to tailor rheological properties for 3D printing

Abstract: Gelatin methacryloyl (GelMA) is a versatile biomaterial that has been shown to possess many advantages such as good biocompatibility, support for cell growth, tunable mechanical properties, photocurable capability, and low material cost. Due to these superior properties, much research has been carried out to develop GelMA as a bioink for bioprinting. However, there are still many challenges, and one major challenge is the control of its rheological properties to yield good printability. Herein, this study pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 34 publications
(41 reference statements)
4
58
0
Order By: Relevance
“…For this reason, modifications of this material are unusual and only Haring et al ( 2019 ) modifieds GelMA with a dopamine molecule. Hence, it appears in 25 papers, it is combined with other selected material in 8 papers, used alone in othersix (Bertassoni et al, 2014 ; Billiet et al, 2014 ; Ersumo et al, 2016 ; Gu et al, 2018 ; Pepelanova et al, 2018 ; Zhou et al, 2019 ), with more than two of the selected materials, and used with other different materials in 5 papers. Alginate is the most common combination of GelMA appearing in 4, 3, and 2 papers for two-, three-, and four-material hydrogels, respectively (further details in the alginate section).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, modifications of this material are unusual and only Haring et al ( 2019 ) modifieds GelMA with a dopamine molecule. Hence, it appears in 25 papers, it is combined with other selected material in 8 papers, used alone in othersix (Bertassoni et al, 2014 ; Billiet et al, 2014 ; Ersumo et al, 2016 ; Gu et al, 2018 ; Pepelanova et al, 2018 ; Zhou et al, 2019 ), with more than two of the selected materials, and used with other different materials in 5 papers. Alginate is the most common combination of GelMA appearing in 4, 3, and 2 papers for two-, three-, and four-material hydrogels, respectively (further details in the alginate section).…”
Section: Resultsmentioning
confidence: 99%
“…Bone marrow stromal cells (BMSCs) and Human umbilical vein endothelial cells (HUVECs) are used in 7 different papers: quantitative analysis (6) (Campbell et al, 2015 ; Irvine et al, 2015 ; He et al, 2018 ; Liu et al, 2018 ; Maiullari et al, 2018 ; Ji et al, 2019 ), and qualitative analysis (1) (Suntornnond et al, 2017 ). On the other hand, C2C12 cells (a myoblast cell line) are used in 6 papers, all of them analyzed quantitatively (Bandyopadhyay et al, 2018 ; Contessi Negrini et al, 2018 ; GarcĂ­a-Lizarribar et al, 2018 ; Li et al, 2018a , b , c ; Zhou et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin methacryloyl (GelMA) has been investigated as a potential alternative to Matrigel Âź for 3D culture systems and bioapplications 10,11 . GelMA is an engineered gelatin-based material that has been proven to be versatile for tissue engineering, drug delivery, and 3D printing applications 12–19 . GelMA displays some important features such as biocompatibility, enzymatic cleavage (degradation in response to matrix metalloproteinases, MMPs), cell adhesion (arginine-glycine-aspartic acid, RGD sequences), and tailorable mechanical properties 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…used enzymatic crosslinking followed by photocrosslinking in order to improve the viscosity of GelMA for bioprinting purposes [30]. They mixed mTGase powder with GelMA and studied the viscoelastic properties of the constructed gels, resulting in better shear thinning properties and improved printability in extrusion-based printing [31]. Both studies demonstrated improved rheological properties of GelMA while enabling the fabrication of the hydrogels in predesigned shapes.…”
Section: Introductionmentioning
confidence: 99%